Effect of mechanical strain on gastric cellular migration and proliferation during mucosal healing: role of Rho dependent and Rac dependent cytoskeletal reorganisation. Issue 4 (1st October 1999) - Osada, T; Watanabe, S; Tanaka, H; Hirose, M; Miyazaki, A; Sato, N
Abstract : BACKGROUND: Various factors affect gastric wound healing. The influence of physical stimulation on gastric mucosal cells during the process of gastric wound healing is not completely understood. AIMS: To assess the role of a physical stimulant, in this case mechanical strain, on gastric mucosal restoration. METHODS: Mechanical strain was applied to adherent rat gastric mucosal cells (RGM1) cultured confluently on collagen type I coated silicone elastomer membrane in order to increase the dimension by an average of 5% and 10% at 5 cycles/minute for 72 hours after wounding. Repair of the wound was monitored every 12 hours for up to 72 hours using an inverted phase contrast microscope. Cell proliferation was detected using 5-bromodeoxyuridine staining. The cytoskeletal protein actin, a component of focal adhesion plaque protein, vinculin, and the small GTP-binding proteins RhoA and Rac1 were detected by immunohistochemistry in the cells located at the margin of and remote from the wound. RESULTS: The cells located at the margin of the wound showed the greatest migration and proliferation and were found to express more rudimentary lamellipodia and filopodia in the absence of mechanical strain. Vinculin, RhoA, and Rac1 were also strongly expressed in the wound margin. Under conditions of mechanical strain, the speed of migration of cells slowed and fewer proliferating cells were detected around the wound in a strain strength dependent manner. Lamellipodial formation, vinculin, RhoA, and Rac1 were poorly expressed in the same area. However, in cells located more than 1 mm from the wound edge, cytoskeletal rearrangement, and the expression of vinculin, RhoA, and Rac1 were not influenced by mechanical strain. CONCLUSIONS: Migration and proliferation of RGM1 cells in culture during wound healing were inhibited by mechanical strain, which caused dysfunction of the cytoskeletal and cell adhesion systems. It is suggested that physical stimulants such as mechanical strain may play a role in gastric wound healing in vivo by modifying cellular migration and proliferation.